2008
DOI: 10.1016/j.tim.2008.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Paramyxoviruses: different receptors – different mechanisms of fusion

Abstract: Paramyxovirus-mediated membrane fusion usually requires an interaction between the viralattachment and -fusion proteins. The mechanism by which this interaction regulates fusion differs between paramyxoviruses that bind to sialic acid-containing receptors and those that recognize specific proteins. The recently solved structure of the globular head of the measles virus hemagglutinin suggests that this difference might be related to the location of the receptor-binding sites on the attachment proteins of the tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
47
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 32 publications
4
47
1
Order By: Relevance
“…The stalk domains of several paramyxovirus HN proteins have been implicated in mediating specificity for their homotypic F proteins (18,20,43,63,70,72). We have found that this extends to MeV and canine distemper virus H and, thus, to paramyxovirinae recognizing proteinaceous receptors (36), supporting the general hypothesis that F-interacting residues may reside in the stalk region of the attachment protein (30,78).…”
supporting
confidence: 67%
“…The stalk domains of several paramyxovirus HN proteins have been implicated in mediating specificity for their homotypic F proteins (18,20,43,63,70,72). We have found that this extends to MeV and canine distemper virus H and, thus, to paramyxovirinae recognizing proteinaceous receptors (36), supporting the general hypothesis that F-interacting residues may reside in the stalk region of the attachment protein (30,78).…”
supporting
confidence: 67%
“…The role of the receptor binding protein has been considered to be mainly repressive for viruses such as measles virus and NiV, where clamping the F protein prevents it from assuming a postfusion structure before the virus engages its proteinaceous receptor (10,12,36,47,(57)(58)(59)(60)(61). In the case of sialic acid binding receptor binding paramyxoviruses, such as HPIV and NDV, en- viruses engage receptor, the receptor binding proteins stabilize the F protein to prevent premature activation, and the switch to an active role in triggering the F protein to fuse occurs upon receptor engagement (17).…”
Section: Discussionmentioning
confidence: 99%
“…However, receptor binding and fusion are mediated by two different glycoproteins, the attachment and fusion (F) proteins, respectively, requiring a mechanism by which the two processes can be linked. This is accomplished by a virus-specific interaction between the two proteins (9,10,13,19).…”
Section: Newcastle Disease Virus (Ndv)-induced Membrane Fusion Requirmentioning
confidence: 99%
“…However, receptor binding and fusion are mediated by two different glycoproteins, the attachment and fusion (F) proteins, respectively, requiring a mechanism by which the two processes can be linked. This is accomplished by a virus-specific interaction between the two proteins (9,10,13,19).The ectodomain of paramyxovirus attachment proteins, including the NDV hemagglutinin-neuraminidase (HN), consists of a long stalk connected to a terminal globular domain (12). Whereas the HN globular domain mediates binding to sialic acid receptors, the stalk mediates the interaction with the homologous F protein (5,15,16).…”
mentioning
confidence: 99%